Accountability in the Third Sector in Puerto Rico (2010-2021): Proposal for a Standardized Report - López-Rodríguez, Luz Mairym (Revista del CLAD Reforma y Democracia, 2025)
In Puerto Rico, the legislative assembly annually grants subsidies to Nonprofit Organizations (NPOs). However, the required accountability is limited to submitting a semi-annual report on the use of allocated funds, which does not establish the expected indicators or the scope of the content. For this reason, the purpose of this qualitative research is to develop a standardized outcome report. Additionally, it aims to determine the actual content of the outcome reports that NPOs submitted to the legislature for fiscal years 2010 to 2021, assessing the integration of the six criteria identified in the literature review. Five NPOs were evaluated, all of which consistently submitted reports. The average compliance rate for submitting reports among these five NPOs was 73 %. The content of the reports met only two of the six evaluated criteria (resources invested and outputs). This study provides an outcome report model with global applicability across all sectors, incorporating the six factors identified in the literature within the logical model framework.